1987
DOI: 10.1084/jem.165.2.515
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 enhances T-dependent immune responses by amplifying the function of dendritic cells.

Abstract: The function of exogenous murine recombinant IL-1 alpha as a T lymphocyte-activating molecule was examined. IL-1 did not induce IL-2 release or responsiveness in purified T cells regardless of their state of activation: unprimed lymphocytes, freshly sensitized lymphocytes, or memory cells derived from the blasts. Nor did IL-1 synergize with mitogens, or with antigens, to stimulate proliferation. For example the combinations of IL-1 plus Ia+ peritoneal macrophages, or IL-1 plus Con A, were less than 5% as effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
2
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(73 citation statements)
references
References 31 publications
5
65
2
1
Order By: Relevance
“…In contrast, other studies have shown that macrophages can increase the sensitivity of MLR to Peyer's patch cells [27]. It is most likely that this effect may be mediated by macrophages production of IL-1 which is not produced by DC [16], but which amplifies DC function [15] and all these factors require further experimental analysis. Although it has been reported in previous studies that an allogeneic MLR can occur without the involvement of IL-1 [23], it is likely that all T cell responses require a number of co-stimulatory factors [11].…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, other studies have shown that macrophages can increase the sensitivity of MLR to Peyer's patch cells [27]. It is most likely that this effect may be mediated by macrophages production of IL-1 which is not produced by DC [16], but which amplifies DC function [15] and all these factors require further experimental analysis. Although it has been reported in previous studies that an allogeneic MLR can occur without the involvement of IL-1 [23], it is likely that all T cell responses require a number of co-stimulatory factors [11].…”
Section: Discussionmentioning
confidence: 89%
“…Although IL-1 has been shown to have a direct costimulatory effect on B cells (6), the data on TI responses appear to indicate that this property is not critical in vivo. The role of IL-1 in TD responses could reflect its ability to directly costimulate T cells (5), as well as indirectly through costimulation of Ag-presenting DC (7). The ability of IL-1 to costimulate chemokine release (53,54) may also help to promote TD immunity.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 plays a key role in mediating innate host protection in response to pathogens, but is also a major inducer of tissue damage during infections and in pathologic conditions such as asthma and various autoimmune diseases (3,4). IL-1 also exerts effects on cells involved in the adaptive immune response, acting directly as a costimulus for T cells (5), B cells (6), and dendritic cells (DCs) 4 (7). In this regard, exogenous IL-1 can act as an adjuvant to enhance Ab production to particulate (8) and soluble protein (9) Ags.…”
mentioning
confidence: 99%
“…Koide et al (31) reported that IL-1 enhances the clustering and T cell stimulatory capacity of spleen DC. Heufler et al (32) found that IL-1 enhances the stimulatory capacity of murine Langerhans cells matured in the presence of GM-CSF.…”
Section: Discussionmentioning
confidence: 99%